2014
DOI: 10.2174/1874088x01408010147
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Tensile Properties of the Steel-Plastic Geogrids

Abstract: Abstract:Tensile strength is an important indicator of the steel-plastic geogrid mechanical properties. Tensile strength directly affects the size of the steel geogrid security and stability in support of the project. Stretching through the indoor geogrid test for combinations of different sizes and different geogrid elongation rate, tensile strength of the geogrid were compared. The findings are as follows: (1)The size of the stretching rate has a significant effect on the tensile properties of steel-plastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Through the regression analysis of tensile strength and tensile rates corresponding to ultimate elongation, it was found that logarithmic regression and power regression had the greatest correlation, but in general, power regression was the best. This analytical method for evaluating the extent to which the tensile strength of geogrids was affected by the tensile rate is similar to that of Yang et al 3 The regression equation and correlation coefficient are shown in Table 7. The regression equation could estimate the tensile strength at a given tensile rate.…”
Section: Regression Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Through the regression analysis of tensile strength and tensile rates corresponding to ultimate elongation, it was found that logarithmic regression and power regression had the greatest correlation, but in general, power regression was the best. This analytical method for evaluating the extent to which the tensile strength of geogrids was affected by the tensile rate is similar to that of Yang et al 3 The regression equation and correlation coefficient are shown in Table 7. The regression equation could estimate the tensile strength at a given tensile rate.…”
Section: Regression Analysismentioning
confidence: 97%
“…2 The study of the tensile strength of geogrids has also become a major project, and the most commonly used test method is the indoor tensile test. In terms of indoor tensile tests, Yang et al 3 investigated the effect of different tensile rates on the tensile properties of HDPE geogrids of three strengths through indoor tests. Hsieh and Lin 4 conducted tensile tests by using single-width geogrids and wide geogrids at different rate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to make the tensile strength-axial strain curves of different morphology parameters of geogrids predictable, this paper establishes a model for the tensile strengthaxial strain of different morphology parameters of geogrids based on the Sherwood-Frost constitutive model 49 (see equation (17)). Similar to regression analysis, this paper only constructs a model for the geogrid tensile strength-axial strain by quantifiable morphological parameters such as filling ratio, rib width, and rib height.…”
Section: Research On the Tensile Strength-axial Strain Model Of Geogridmentioning
confidence: 99%
“…10 Currently, the most common test method for the tensile properties of geogrids is the indoor tensile test. In terms of geogrid tensile tests, the existing literature mostly analyzes the effects of tensile medium, [11][12][13][14][15] tensile rate 16,17 and different ambient temperatures [18][19][20] on the tensile properties of geogrids. Balakrishnan and Viswanadham 21 found that the tensile load-strain behaviour of geogrids improved, and their tensile stiffness increased by a maximum of 2.42 times after tensile tests on geogrids inside the soil.…”
Section: Introductionmentioning
confidence: 99%